Análise de distribuição espaço-temporal da neblina no Litoral Norte do Parque Estadual Serra do Mar - Chaverri, Andrés Gabriel Arguedas (2025)
Fog detection has been widely studied for decades, both for its ecological significance and its various impacts on human activities. While substantial advances have been made in satellite-based detection methodologies, knowledge gaps persist in understanding fog formation patterns in different regions worldwide. This study aims to analyze the spatiotemporal dynamics of fog in the Northern Coast of the Serra do Mar State Park (PESM), São Paulo. The research is structured into three chapters. The first chapter presents a literature review on fog and low-stratus (FLS) detection using satellite imagery. The second chapter investigates changes in fog frequency over time by developing an algorithm based on MODIS satellite data within the Google Earth Engine (GEE) platform. The third chapter characterizes the fog formation process and its spatial distribution within the study area, analyzing the topographic and climatic variables influencing this phenomenon. The literature review highlighted a recent trend in publications focusing on fog forecasting methods over marine environments and spatiotemporal patterns in ecosystems vulnerable to climate change. The fog frequency analysis revealed an increase during winter, with potential contributing factors discussed, along with their impact on local hydrological processes. In the third chapter, results indicated that fog in the study area is predominantly orographic, driven by the interaction between irregular topography, temperature, and wind patterns. This increase is potentially linked to climate change and the role of native forests in maintaining humidity and enhancing fog formation. Wind patterns, terrain heterogeneity, and land surface temperature (LST) in forested areas create a favorable environment for fog development, particularly of the orographic type.